The Effect of Financial Compensation, Supervision and Job Stress on Employee Performance at PT Fajar Abadi Jaya Perkasa Medan - Melkyory Andronicus; Elly; Ricky Gunawan; Kalvin Kusumo (Journal of Research in Business, Economics, and Education, 2020)
Researchers took the object of research from PT Fajar Abadi Jaya Perkasa. Declining performance experienced by the company at this time. Financial compensation is a payment received in the form of employee benefits. From the data it appears that receiving different basic gifts and bonuses are received by employees and not in accordance with the length of service given to different employees from one position with the same division. Supervision is the control of the leadership of the work of employees. From routine error data every month Job stress is a level of stress experienced by employees at work. From the data that can be seen in May 2018, resignation occurred as many as 4 people who considered several reasons such as conflicts with colleagues, did not require leave permission, there were duplicate jobs, incentives that were often late received. The number of participation as many as 65 people and 30 people were taken from PT Sukses Usaha Nirwana for validity test. The research method used is quantitative with quantitative descriptive research. Methods of data collection by interview, distribution of questionnaires and study of documentation. The analytical method used is multiple linear regression, coefficient of determination and simultaneous testing (F-Test) (21,772> 3,15) with values and partial (t-test) (3,691> 1,983), (2,043> 1,983) and (4,631>> 1,983). The results showed that financial comparison, supervision, simultaneous and partial work stress had a significant positive effect on employee performance with a coefficient of determination of 49.3%.